Plant species Diversity of Woody Species in Community Forest of East Khasi Hills District Meghalaya, North East India - Iangrai, Larikynti; Chaturvedi, Shiva Shankar (Indian Forester, 2025)
Woody species diversity and community characteristics of community forest were investigated in East Khasi Hills District Meghalaya, North Eastern India. A total of 144 species were recorded belonging to 94 genera and 58 families in the four community forests. The Shannon-Wiener Index (H’) of the tree species in the four forest stands ranged from 1.59 to 3.48, Simpson’s dominance index from 0.02 to 0.07, evenness index from 0.80 to 0.89 and Margalef index ranges from 4 to 10. The density of woody species ranged from 788 to 1624 trees ha-1. The dominant families includes Lauraceae with 17 species, Fagaceae with 11 species and Moraceae with 11 species. The study provides significant insights into the species variety and community structure of trees that are present in the community forest which is essential for effective management and preservation of the forests.